EFISIENSI FAKTOR-FAKTOR PRODUKSI USAHATANI BAWANG MERAH KELOMPOK TANI â€œSUKA TANIâ€ DI DESA BLUMBANG KECAMATANTAWANGMANGUKABUPATEN KARANGANYAR - Dwi Wahyuni; Suswadi Suswadi; Kusriani Prasetyowati (JURNAL ILMIAH AGRINECA, 2018)
Agricultural development is not his time anymore if only oriented to a certain food commodities, but it should be able to give priority to other food commodities. The role of agriculture as a seed sector are vital in driving national economic development. One effort to improve agriculture's contribution is the development of horticultural crops. Horticulture development is part of the overall agricultural development that was developed to be able to meet the needs of the market.The rearch ordering to analyze the greatest affecting of production factors to the production result in onion farm in Blumbang Recency and to find out whether the farmer in Blumbang Regency hadÂ  reached the highest economic efficiecy. The main method of research was descriptive and the techique was by using survey. The result of the double-linier regression analysis performed that the productionÂ  factor which gave the greatest affecting to the result of onion production is larger land. Based on the maximum profid approach caan be found out taht the combination of the use of production factors in onion farm in Blumbang Regency not yet optimal. It means that onion farm needs combination of increasing and or descreasing production factors to the use of production factor.